Confessions of an amateur sleuth - Cahoon, Lynn (Cahoon, Lynn. Bainbridge Island mystery series, 2026)
"Twenty-something bookseller and sleuth Meg Gates has a confession: solving crimes may be easier than writing. She's been working on a guide to becoming a detective--but she's her own worst critic. She needs a how-to in order to write her how-to! At the Bainbridge Island writers' group, she meets freelance food critic Lee Anderson, who invites her to join him for dinner at the Local Crab so he won't be suspected of reviewing the place. Lee is a bit of a crab himself and intends to do a hatchet job on the eatery. Instead, someone does a job on the critic--he's found dead by the marina. Now Bainbridge's culinary elite are on the suspect list. With help from her beau, Dalton, and the Mystery Crew at Island Books, Meg dons her sleuthing cap to solve the mystery du jour--before another murder is served cold . . ." --